Automatic quantification of displacement and ring generalship during high-level elite boxing competitions - Schortgen, A.; Goyallon, T.; Reveret, L.; Moussa, I.; Sauliere, G.; Brezephin, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Ring generalship (RG), or ring occupancy, is an essential key performance indicator in elite boxing. Understanding position and movement of an opponent leads to defining better strategies, controlling the pace of the bout and imposing advantageous fighting ranges [1]. In addition to landed strikes, effective pressure and defense, RG influences the final score. Due to the high-intensity nature of boxing, fatigue is directly related to punch effectiveness as well as stances, even if the latter is significantly less studied in the literature. To date, little has been made available to measure and analyze the concept of RG in real-life scenarios, especially using automatic method to avoid any bias. The purpose of this study is to accurately track fighters locations inside the ring and extract relevant metrics.